2015
DOI: 10.1177/0363199015602929
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of Marriages in the Sajkaska Region (North Serbia), 1869 to 2011

Abstract: This article studies monthly distribution of marriages in Sajkaska region (North Serbia) for the period 1869 to 2011. The data were derived from 64,175 marriages that are found in marriage registers. For the purpose of the analysis, the entire period is divided into seven smaller periods. The main finding of this article is that seasonality of marriage changed along with the system of production. Also, adherence of religion played an important role in the past. At the beginning of the period of our analysis, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…With regard to Advent, he found that celebrants began to ignore this ban in the early twentieth century. Likewise, Arsenovic et al (2015) concluded that, in Sajkaska (Republic of Serbia), religion had a huge impact on seasonality up to the twentieth century.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to Advent, he found that celebrants began to ignore this ban in the early twentieth century. Likewise, Arsenovic et al (2015) concluded that, in Sajkaska (Republic of Serbia), religion had a huge impact on seasonality up to the twentieth century.…”
Section: Introductionmentioning
confidence: 99%